KOMPENSASI DAN KEPUASAN KERJA SEBAGAI ALTERNATIF PENINGKATAN KINERJA KARYAWAN - NAILIN NIKMATUL MAULIDIYAH; Tri Nadhirotur Rofish; Nuruddin Armanto (Al-Idarah, 2021)
This study aims to determine the effect of compensation on employee performance and the effect of job satisfaction on employee performance. This research is a qualitative research which is sourced from existing theories and relevant empirical research journals. The results of this study showed that compensation has a positive effect on employee performance and job satisfaction has a positive effect on employee performance.